Action and Communication in Niklas Luhmann’s Social Theory - Salem, A. (Sociologija. Mintis ir veiksmas, 2013)
This article offers a critical introduction to some of the most striking features of Niklas Luhmann’s social theory. It opens with a discussion of Luhmann’s departure from older forms of functionalism (above all the ideas of Parsons), and of how his work marks a distinct break with essentialism, foundationalism and humanism. This is followed by an account of the importance to his theory of free-form social structures that can reproduce themselves in ways not determined by external forces, a never-ending process in which, on Luhmann’s account, human agents have no part to play. Next the place and role of communication (and of obstacles to communicative efficacy) in his vision of society are examined, and the decisive split between human action and communication systems in his work is further discussed. Finally, some of the implications of Luhmann’s theory for social critique are drawn out, and it is argued that, despite posing serious difficulties for the idea of criticism as conventionally conceived, this theory might actually help to renew it. Keywords: communications theory, cybernetics, human action, post-humanism, social change, social criticism, social systems, social theory.